ABUNDANCES OF THE ELEMENTS: METEORITIC AND SOLAR - Anders E.; Grevesse N. (My University, 1989)
New abundance tables have been compiled for Cl chondrites and the solar photosphere and corona, based on a critical review of the literature to mid-1988. The meteorite data are generally accurate to ± 5–10%. Significant discrepancies between Sun and meteorites occur only for Fe, Mn, Ge, Pb, and W; other well-determined elements agree to ±9% on the average. There is no evidence for group fractionations in Cl chondrites of cosmochemically similar elements (refractories, siderophiles, volatiles, etc.), but a selective fractionation of Fe cannot be ruled out. Abundances of odd-A nuclides between A = 65 and 209 show a generally smooth trend, with elemental abundances conforming to the slope defined by isotopic abundances. Significant irregularities occur in the NdSmEu region, however, suggesting that the abundance curve is dependably smooth only down to the ~20% level